Development and characterization of an exposure platform suitable for physico-chemical, morphological and toxicological characterization of printer-emitted particles (PEPs). (June 2014) - Pirela, Sandra V.; Pyrgiotakis, Georgios; Bello, Dhimiter; Thomas, Treye; Castranova, Vincent; Demokritou, Philip
Abstract An association between laser printer use and emissions of particulate matter (PM), ozone and volatile organic compounds has been reported in recent studies. However, the detailed physico-chemical, morphological and toxicological characterization of these printer-emitted particles (PEPs) and possible incorporation of engineered nanomaterials into toner formulations remain largely unknown. In this study, a printer exposure generation system suitable for the physico-chemical, morphological, and toxicological characterization of PEPs was developed and used to assess the properties of PEPs from the use of commercially available laser printers. The system consists of a glovebox type environmental chamber for uninterrupted printer operation, real-time and time-integrated particle sampling instrumentation for the size fractionation and sampling of PEPs and an exposure chamber for inhalation toxicological studies. Eleven commonly used laser printers were evaluated and ranked based on their PM emission profiles. Results show PM peak emissions are brand independent and varied between 3000 to 1 300 000 particles/cm3, with modal diameters ranging from 49 to 208 nm, with the majority of PEPs in the nanoscale (<100 nm) size. Furthermore, it was shown that PEPs can be affected by certain operational parameters and printing conditions. The release of nanoscale particles from a nano-enabled product (printer toner) raises questions about health implications to users. The presented PEGS platform will help in assessing the toxicological profile of PEPs and the link to the physico-chemical and morphological properties of emitted PM and toner formulations.